(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
A research investigation was conducted at Kirkuk University between October 14, 2019, and December 9, 2019, to assess the effects of different doses of licorice plant leaf powder on white chickens. There was a control group that did not get any additives, and there were five groups of twenty-eight hens each that were given different doses of licorice (0.1%, 0.25%, 0.5%, and 0.75%). There was a considerable statistical disparity observed among some treatments in the initial phases of egg development, but no corresponding disparity in the average weight of the eggs. The egg mass rate during the second period is significantly distinct from that of the fifth treatment. Typically, the treatment is ranked between fourth and sixth out of all therapies. There is a notable disparity in the rate at which feed is consumed between the first and subsequent intervals, whereas the total rate stays consistent in the fourth and fifth treatments. There is a significant disparity between the third and fifth treatment sessions. We did not observe any significant fluctuations in the food conversion rate, high white and unit Hu, or average shell weight. We noticed a statistically significant difference in the rate of the relative weight of white between the fifth treatment group and the control group in the first two periods, as well as in the third, fourth, and fifth periods. Treatment five exhibited a statistically significant alteration compared to treatments two and three in terms of the overall rate and relative yolk weight. The diameter of the yolk exhibited a substantial deviation from the overall average in treatment number five, while the high yolk rate showed a considerable difference compared to treatments three, four, and five. There was a substantial statistical difference in the rate of shell thickness between the fifth treatment and the first two sessions, as well as between the fourth and fifth periods. Treatments 3, 4, and 5 exhibited significant variations in their total rates. Glucose and uric acid levels are elevated, although cholesterol, total protein, and choline levels are comparable.